2022
DOI: 10.1093/europace/euac053.018
|View full text |Cite
|
Sign up to set email alerts
|

Additional features in Brugada Syndrome stratification: frequent PVC and QRS duration

Abstract: Funding Acknowledgements Type of funding sources: None. Introduction Brugada syndrome (BrS) is a channelopathy with high prevalence of malignant arrhythmic events. The risk stratification in patients (pts) with Brugada electrocardiographic (ECG) pattern is of major importance, to prevent sudden cardiac death (SCD). A higher risk is evidenced in spontaneous type 1 pattern when compared with induced type-1 pattern, as so other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Prolonged QRS has been associated with a higher incidence of symptoms and ventricular arrhythmias. [24][25][26] BrS often shows complex inheritance with incomplete penetrance and variable expressivity. 27 Data from the literature have suggested that the presence of SNPs might influence the clinical expression of SCN5A pathogenic mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged QRS has been associated with a higher incidence of symptoms and ventricular arrhythmias. [24][25][26] BrS often shows complex inheritance with incomplete penetrance and variable expressivity. 27 Data from the literature have suggested that the presence of SNPs might influence the clinical expression of SCN5A pathogenic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged QRS interval has been attributed to sodium current dysfunction mainly in the conduction system and specifically in the His-Purkinje system. Prolonged QRS has been associated with a higher incidence of symptoms and ventricular arrhythmias 24–26 …”
Section: Discussionmentioning
confidence: 99%